The Influence Of Financial Literacy And E-Money Use On The Consumer Behavior Of Students In The Management Study Program At Lamappapoleon University - Sukma Aini; Masyadi Masyadi; Mutmainna Andi Sudirman; Ika Mahkota Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The background of this research problem is to determine the influence of financial literacy and e-money use on the consumer behavior of students in the Management study program at Lamappapoleonro University. This research is classified as quantitative. The data sources are secondary data. The data analysis method used is multiple linear regression. Furthermore, the hypothesis was tested using the F-test, t-test, and coefficient of determination. The results of this study indicate that financial literacy and e-money use significantly influence the consumer behavior of students in the Management study program at Lamappapoleonro University